Analysis of the Digital Competence in the Initial Formation of University Students: A Meta-Analysis Study on the Web of Science [Análisis de la Competencia Digital en la Formación Inicial de Estudiantes Universitarios: Un Estudio de Meta-Análisis en la Web of Science] - Silva-Quiroz, J; Abricot-Marchant, N (Universidad de Sevilla, 2020)
In recent years the scientific production around the Digital Competition has had an exponential growth, deepening mainly in the study of the self-perception on the level of expected development or the evaluation / diagnosis of the domain in said area. The objective of this article is to know what instruments are used and what aspects are evaluated in the investigations that seek to recognize the digital skills of new university students through a meta-analysis in WoS established for the 2014-2019 interval and using keywords categorized into three areas: “Digital Competences”, “Students” and “Evaluation”, with the ultimate goal of establishing hypotheses that include variables that have not been taken into account up to now about the instruments that are being used and the aspects that are evaluated. As the main conclusion, we advance that two main views have been found: perceptive and performance. This highlights the importance of encouraging studies that combine both approaches. © 2020 Universidad de Sevilla. All rights reserved.